Don't Get Your Hopes Up: Avoidantly Attached Individuals Perceive Lower Social Reward When There Is Potential for Intimacy. (February 2013) - Spielmann, Stephanie S.; Maxwell, Jessica A.; MacDonald, Geoff; Baratta, Patricia L.
We examine whether lower expectations for social reward selectively applied to high intimacy contexts may help avoidantly attached individuals minimize distress from reward loss. Studies 1, 2, and 4 demonstrated that avoidant attachment was negatively associated with perceived intimacy potential in relationships involving approach of closeness (current/future partners), but not for relationships less associated with approach of closeness (ex-partners). Studies 3 and 5 manipulated the potential for intimacy among dating prospects. Avoidant attachment was negatively associated with romantic interest in high intimacy targets but not low intimacy targets. This effect was mediated by perceived responsiveness. Studies 4 and 5 rule out perceived dissimilarity to responsive targets as a mechanism. Study 6 demonstrated that avoidants' lower expectations for connection are associated with less anticipated distress from reward loss. These results suggest that avoidant individuals may circumvent attachment system activation by perceiving lower opportunity for connection when there is potential for intimacy.